The Effect of Listening Comprehension through Podcast among Indonesian Pre-Intermediate EFL Learners - Heki Hamdani; Zahratul Fikni; Baiq Suprapti Handini (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2022)
This research is aimed at investigating the influence and students’ perception of podcast on students’ listening skill in university level. This research involved twenty students of fourth semester of English Education Research Program at a private university in Nusa Tenggara Timur as participants. The instruments utilised to collect data in this research were the pre- and-post-test. In addition, a survey questionnaire was distributed to students to investigate their perspectives on the use of podcast in teaching listening. Quantitative and qualitative method design was applied in this research. Findings revealed that there is a significance difference between pre- and-post-test results. Data analysis utilising the paired samples test revealed that the significance value (sig. 0.00) is less than 0.05, implying that the Podcast has a substantial impact on students' listening comprehension. Additionally, according to the results of the research, students who participated agreed that they liked podcasts because they helped them acquire listening skills. Podcasts featured amazing subjects and activities that granted both lecturers and students to expand their understanding and enhance their English skills for academic reasons.